David Brackett, Categorizing Sound: Genre and Twentieth-Century Popular Music, Oakland, California 2016 - Karolina Skalska (Muzyka, 2018)
Recenzja książki: David Brackett, Categorizing Sound: Genre and Twentieth-Century Popular Music, Oakland, California 2016